A eficácia dos programas de governo da área de segurança pública no Amazonas: uma análise a partir das metas estabelecidas no Plano Plurianua - Lopes, Luciane Cavalcante (2020)
Public security in Amazonas is one of the areas that demand the most attention from the State and, consequently, where significant amounts of public resources are applied. In this sense, government action requires planning and the Multi-Year Plan (PPA) is presented as one of the instruments that assist in this function, given that it contemplates the objectives and goals of the government for a period of four years. However, it is important to know how effective the State has been in this regard and whether its goals have been achieved in recent years. Thus, considering the content of the Government of Amazonas Multi-Year Plans for the periods 2012-2015 and 2016-2019, the present research consisted of analyzing the performance regarding the effectiveness of the budgetary actions outlined in these plans. Through indicators based on physical goals (Physical Goal Indicator - IMF) and financial (Financial Goal Indicator - IMD) defined for the actions and programs of the multi-year plans selected for study and, using descriptive and inferential statistics techniques analyzes of the collected data were developed, collected especially from the Annual Evaluation Reports. From the result of the Hypothesis Testing with the average of the indicators (T Test), no significant differences in performance were identified between the plans analyzed. During the period of effectiveness of each plan, changes in the planned actions were found, which even resulted in the discontinuation of programs. As for effectiveness, most of the budgetary actions analyzed did not reach the physical and financial goals proposed in the PPA in its initial version. There was also evidence of undersizing targets that impacted the results of the indicators of some actions. Budgetary actions were also identified without any disbursements made during the period of effectiveness of the plans. It is important to note that the present research was limited to a quantitative analysis of the data collected, without going into depth regarding the effectiveness of the actions studied and any influences of external and internal factors, which may be the object of future research studies. The research is expected to contribute to promoting the monitoring of government actions, being useful for public managers, supervisory bodies and society.